Investigation of Alternative Therapeutic and Biocidal Options to Combat Antifungal-Resistant Zoonotic Fungal Pathogens Isolated from Companion Animals - Elaine Meade; Micheal Savage; Mark Slattery; Mary Garvey (Infectious Disease Reports, 2021)
Fungal skin infections and iatrogenic disease of companion animals continue to be an ongoing issue for veterinarians, where misdiagnosis or inapt medical treatment result in secondary conditions within animals. The widespread use of antifungals in both modern medicine and agriculture has resulted in concomitant resistance in species, where zoonotic transfer poses a risk to public health. Studies described herein assess the resistance of pathogenic species isolated from companion animals to a battery of conventional antimicrobial agents. Levels of resistance were detected using recognised in vitro methods, where additional novel therapeutic and biocide options were also extensively investigated. Results show high levels of resistance to the three main families of antifungal agents, namely caspofungin, Amp B and fluconazole. Resistance in Candida, Cryptococcal, Aspergillus and Trichophyton species is described herein, highlighting the need for defined species-specific antifungal breakpoints, and for Malassezia and Wickerhamomyces anomalus species which also have zoonotic potential. Novel compound phendione showed promising antimicrobial activity, with MICs determined for both fungal and bacterial species. The biocidal options investigated also showed potential to act as intermediate-level disinfectants, where peracetic acid proved most effective against fungal spore formers.